Application Of The Two Stay-Two Stray Cooperative Learning Model In Arabic Learning In Mts Fatihul Ulum Al-Mahfudz Manggisan Tanggul: Penerapan Metode Two Stay-Two Stray dalam Pembelajaran Bahasa Arab di Mts Fatihul Ulum Al-Mahfudz Manggisan Tanggul - Fatullah, Iqbal; Mohammad Ainun Rofiq; Dzurratul Qomariyah; M Uzaer Damairi (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2023)
This study's research focus is applying the two Stay-two-study methods in Arabic language learning at Mts Fatihul Ulum Al-Mahfudz Manggisan Tanggul. The research method used in this study is a descriptive qualitative approach. This type of research is a case study. The subjects of the study were selected in a Purposive way. Data collection uses three techniques, namely observation, interview, and documentation. The data analysis used is descriptive. The validity of the data uses triangulation of sources and techniques. Research Results: 1) Preparation for the application of the two stay-two stray method by a) Making a Learning Implementation Plan (RPP), b) Preparation of Media to be used in class, c) Preparation of teaching materials to be delivered in class d) Preparing learning strategies to be applied in class. 2) The process of applying the two stay-two-stray methods in Arabic Learning, namely, initial activities which include: a) conveying learning objectives, b) conveying the learning methods to be used, and c) explaining the introductory material about commendable morals. Core Activities are a) conveying information to students, b) forming students into groups, and c) guiding groups to work together. The closing activities convey conclusions and reflections on learning. Keywords: Cooperative learning, Two stay-two-stray method, Arabic Language Learning  Abstrak Penelitian ini adalah Bagaimana Proses Penerapan Metode Two Stay-Two Stray dalam Pembelajaran bahasa Arab di MTs Fatihul Ulum Al-Mahfudz Manggisan Tanggul. Metode Penelitian yang digunakan dalam penelitian ini adalah pendekatan kualitatif deskriptif. Jenis penelitian ini adalah studi kasus. Subjek penelitian dipilih dengan cara Purposive. Teknik pengumpulan data menggunakan tiga teknik yaitu observasi, wawancara dan dokumentasi. Analisis data yang digunakan adalah analisis deskriptif. Keabsahan datanya menggunakan triangulasi sumber dan teknik. Hasil Penelitian: 1) Persiapan penerapan metode two stay-two stray dengan cara: a) Pembuatan Rencana Pelaksanaan Pembelajaran (RPP) b) Persiapan Media yang akan digunakan dikelas c) Persiapan Materi ajar yang akan di sampaikan dikelas d) Mempersiapkan strategi pembelajaran yang akan diterapkan dikelas. 2) Proses Penerapan metode two stay-two stray dalam pembelajaran bahasa arab yaitu: kegiatan awal yang meliputi: a) menyampaikan tujuan pembelajaran, b) menyampaikan metode pembelajaran yang akan digunakan, c) menjelaskan materi dasar tentang akhlak terpuji. Kegiatan Inti, yaitu: a) menyampaikan informasi kepada siswa, b) membentuk siswa menjadi beberapa kelompok, c) membimbing kelompok untuk bekerjasama. kegiatan penutup yaitu: menyampaikan kesimpulan, refleksi terhadap pembelajaran. Kata Kunci: Pembelajaran Kooperatif, Metode two stay-two stray, Pembelajaran Bahasa arab